A gene catalogue of the amphioxus nervous system - Benito-Gutiérrez, Èlia (Ivyspring International Publisher, 2006)
The elaboration of extremely complex nervous systems is a major success of evolution. However, at the dawn of the post-genomic era, few data have helped yet to unravel how a nervous system develops and evolves to complexity. On the evolutionary road to vertebrates, amphioxus occupies a key position to tackle this exciting issue. Its “simple” nervous system basically consists of a dorsal nerve cord and a diffuse net of peripheral neurons, which contrasts greatly with the complexity of vertebrate nervous systems. Notwithstanding, increasing data on gene expression has faced up this simplicity by revealing a mounting level of cryptic complexity, with unexpected levels of neuronal diversity, organisation and regionalisation of the central and peripheral nervous systems. Furthermore, recent gene expression data also point to the high neurogenic potential of the epidermis of amphioxus, suggestive of a skin-brain track for the evolution of the vertebrate nervous system. Here I attempt to catalogue and synthesise current gene expression data in the amphioxus nervous system. From this global point of view, I suggest scenarios for the evolutionary origin of complex features in the vertebrate nervous system, with special emphasis on the evolutionary origin of placodes and neural crest, and postulate a pre-patterned migratory pathway of cells, which, in the epidermis, may represent an intermediate state towards the deployment of one of the most striking innovative features of vertebrates: the neural crest and its derivatives.